Sorcin induced multi-drug resistance: an in-silico analysis of interaction between p-glycoprotein (clip protein) and sorcin (calcium binding protein) - R. LOKESH,; C. MAHALAKSHMI,; S.VENKATESH, (International Journal of Pharma and Bio Sciences, 2017)
Role of calcium binding protein (sorcin) in regulation of p-glycoprotein activity has been studied well. Studies on multi drug resistant protein (p-glycoprotein) and its function in cancer are dated for several decades, and yet its complete mechanism is unclear. Suppressing the expression and/or inhibition of sorcin has proven to reduce the p-glycoprotein mediated drug resistance in cancer cells. To understand the interaction association between the sorcin and p glycoprotein, this protein-protein interaction study was carried out using bioinformatic approach. Our results indicate that, sorcin is binding with p-glycoprotein at key regulatory sites, i.e., Transmembrane Domain (TMD) and Nucleotide binding Domain (NBD) that are essential for p-glycoprotein activity. This lead to the hypothesis that, binding of sorcin at the TMD and NBD induces conformational changes to p-glycoprotein, leading to prolonged shuttling of drug molecules from the cell. Verapamil and Reserpine has proven to be sensitive to multi drug resistant (MDR) cancer cells. Our Docking studies suggest that, Verapamil and Reserpine inhibit sorci n, there by leading to inactivation of p glycoprotein, thus negating the p-glycoprotein derived MDR. These findings strongly suggest that, binding of sorcin to p-glycoprotein (at TMD and NBD) leads to MDR in cancer cells.